2002
DOI: 10.1007/bf02987421
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of dimethylphenols by bacteria with different ring-cleavage pathways of phenolic compounds

Abstract: The biodegradation of 3,4, 2,4, 2,3, 2,6 and 3,5-dimethylphenol in combination with phenol and p-cresol by axenic and mixed cultures of bacteria was investigated. The strains, which degrade phenol and p-cresol through different catabolic pathways, were isolated from river water continuously polluted with phenolic compounds of leachate of oil shale semicoke ash heaps. The proper research of degradation of 2,4 and 3,4-dimethylphenol in multinutrient environments was performed. The degradation of phenolic compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…LCW to use only 3,4- and 2,3-DMP as a carbon source, and to remove 3,5-, 2,5- and 2,4-DMP by co-metabolic transformation. Similar co-metabolic transformation of 2,4-, 3,4- and 3,5-DMP has been reported for different strains of Pseudomonas [ 9 ] and C. testosteroni CPW301 [ 27 ]. It was also reported that C. testosteroni CPW301 was able to partially degrade 2,5- and 3,5- DMP by co-metabolism when growing with 4-CP and 4-MP [ 26 ].…”
Section: Discussionsupporting
confidence: 80%
“…LCW to use only 3,4- and 2,3-DMP as a carbon source, and to remove 3,5-, 2,5- and 2,4-DMP by co-metabolic transformation. Similar co-metabolic transformation of 2,4-, 3,4- and 3,5-DMP has been reported for different strains of Pseudomonas [ 9 ] and C. testosteroni CPW301 [ 27 ]. It was also reported that C. testosteroni CPW301 was able to partially degrade 2,5- and 3,5- DMP by co-metabolism when growing with 4-CP and 4-MP [ 26 ].…”
Section: Discussionsupporting
confidence: 80%
“…Intermediates of a catabolic pathway of one strain (e.g., strain PC18) may be further degraded by another strain (e.g., strain PC24) possessing suitable catabolic pathway. Additionally, in strain PC18, catechol meta and protocatechuate ortho pathways are induced with phenol and p ‐cresol, respectively[25], and this strain can decompose dimethylphenols in the presence of phenol and p ‐cresol[4].…”
Section: Discussionmentioning
confidence: 99%
“…Catabolic pathways operating in natural communities reflect interactions between microbial species under mixed culture conditions where extensive sharing of nutritional resources is common[2] and interaction of two or several strains is often a prerequisite for growth and biodegradation[3]. It has already been shown that a mixed culture of strains with different catabolic types overcomes incompatibilities in degradation of divergent substrate mixtures[4]. Among multitude of microbial species in the environment, few populations that can use specific substrates become dominant, while others exist as minorities[5].…”
Section: Introductionmentioning
confidence: 99%
“…This is followed by the formation of an ester function through a mechanism similar to Baeyer-Villiger oxidation (an organic reaction in which a ketone is oxidized to an ester by treatment with peroxy acids or hydrogen peroxide). This ester function is easily cleaved by a mechanism of hydrolysis to yield an alcohol and an aldehyde (Kim et al, 2005;Viggor et al, 2002), which is further reduced in Benzaldehyde, 4-methoxy.…”
Section: Resultsmentioning
confidence: 99%